KEMAMPUAN ANALISIS SISWA DALAM DIMENSI TIGA DIKAJI DARI TINGKATAN BERPIKIR VAN HIELE - Wira Pratama; Edy Yusmin; Asep Nursangaj (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study aims to describe the analysis capabilities of students in the three-dimensional subject matter studied from the level of the thinking of Van Hiele in grade XII MIPA 1 of  SMA Negeri 4 Pontianak. The method used in this research is descriptive method with descriptive qualitative research. Subjects in this study were six students of grade XII MIPA 1 of SMA Negeri 4 Pontianak. The results of the research indicate that two students at the thinking level of visualization and two students at the thinking levels of analysis have not been able to find the indicators of the ability of analysis, while two students at the thinking level of abstraction is only one student who is able to find the indicators of the ability of the analysis.Keywords: Analytical Skills, Three-Dimensional, Levels of Thinking by Van Hiele